Analisis Trend sebagai Media untuk Menaksir Kinerja Keuangan Pada PT Media Nusantara Citra Tbk - Tanti Pratiwi; Hari Sulistiyo (Jurnal Akuntansi dan Keuangan, 2023)
ABSTRACTOne of the activities or the final task that is important for an investor or a management is to review the company's financial statements that need to be carried out carefully to be able to make the right decision. Financial reports that have been arranged by a company can be used to quote a decision, both for internal and external administrative parties of the company. Financial statements are the most recent procedure in accounting which has a very important role to measure & evaluate the performance of a company. Especially companies located in Indonesia that have gone public, should manifest financial reports every year. The purpose of this observation is to understand the financial performance of PT Media Nusantara Citra Tbk based on the financial reports that have been prepared for the past year. The financial report data is obtained from the annual financial reports, namely from 2019-2021 and will be analyzed or observed using trend analysis. The analysis technique used in this observation process is intended to use a quantitative approach, because the data is in the form of financial reports that are in accordance with the actual situation of the observations being investigated. The results of this observation are to understand and evaluate what the financial performance of PT Media Nusantara Citra Tbk is like in terms of increasingÂ